PENGARUH BUNGA DEPOSITO DAN NILAI TUKAR TERHADAP PENDAPATAN PERKAPITA DI INDONESIA (1995-2017) - Francisca Sestri Goestjahjanti (Business Management Journal, 2019)
The purpose of this study is to analyze and assess the magnitude of simultaneously and partially influence of deposit interest and exchange rates to income per capita in Indonesia. This research used secondary data time series for 23 years since 1995 up to 2017. The study method used explanatory research to explain the causal relationship between the variables in a model through hypothesis test. The analyzes employed statistical technique of linear regression with the software E-Views 7 and SPSS-22.The results of the study showed that these variables time deposit rate and xchange rate are simultaneously and partially give significant effects to income percapita in Indonesia period 1995-2017 Keywords : Time deposit rate, Exchange rate, Income per Capita.